Prediksi Harga Emas Batang Menggunakan Feed Forward Neural Network Dengan Algoritme Genetika - Dimas Fachrurrozi Azam; Dian Eka Ratnawati; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Investment is an activity to buy goods, with the purpose to be sold to other investors until they reach a high enough value. There are many types of investments, one of which is gold. Some people who are just starting out in investing find it difficult in deciding to buy and sell gold. Many losses will be obtained if the investor missteps in selling or buying gold. Based on the problem, the researcher intends to help the investor by proposing gold price prediction system using feed forward neural network (FFNN) with genetic algorithm. The genetic algorithm method is used to optimize the existing weights to be used with the forward neural network feed model to process the price prediction. From the test result, the total of 126 training data, and the total of 54 testing data, the CR value 0.3 and the MR value 0.7, the number of pop size is 250, the number of generations are 200, yields an average mean root mean square error (RMSE) of 0.304587%.